Communication Strategy of Social Studies Teachers in Integrating Climate Change Issues in Semarang - Lukitawati, Lukki; Hermanto, Fredy; Rusdini, Siti Ekowati; Winanto, Zabidi Agus (Universitas Negeri Semarang, 2025)
This study examines how Social Studies teachers in Semarang, Indonesia, frame and communicate climate change issues through the lenses of environmental communication and ecopedagogy. Drawing on a structured online survey of 116 I teachers from Musyawarah Guru Mata Pelajaran Ilmu Pengetahuan Sosial Semarang, the research identifies four perceptual constructs: awareness, knowledge, perception, institutional responsibility, and self-efficacy. It classifies the topics teachers choose into pragmatic mitigation measures or constitutive identity‐building issues and their strategies, e.g., class discussions, project-based learning, visual media, and policy advocacy. Descriptive analyses show that while teachers recognize climate change and its future risks (means ≥ 4.18/5), they tend to favor conventional, one-way informational methods alongside participatory projects. By mapping these practices onto Kahn's three-dimensional ecopedagogy, cosmological, technological, and organizational, the study reveals both strengths in building planetary consciousness and gaps, including overreliance on deficit-model framing and limited cultural contextualization. The findings underscore the need for IPS curricula to integrate deliberative, community-centered pedagogies and professional development that apply critical, context-sensitive ecopedagogical practice.